2013
DOI: 10.2478/intox-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of adverse drug reaction monitoring system in a tertiary care teaching hospital in Mumbai, India

Abstract: Adverse drug reactions (ADR) are a significant cause of morbidity and mortality, often identified only post-marketingly. Improvement in current ADR reporting, including utility of underused or innovative methods, is crucial to improve patient safety and public health. Hospital-based monitoring is one of the methods used to collect data about drug prescriptions and adverse events. The aims of this study were to identify the most frequent ADRs recognized by the attending physicians, study their nature, and to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 17 publications
10
34
2
2
Order By: Relevance
“…This was in accordance with the previous studies by Patidar et al, 12 Murphy and Frigo, 14 and Lobo et al, 15 but differed from studies carried out by Lin and Lin. 16 The reason may be higher number of adults visiting the hospital outpatients department or being hospitalized and dose adjustments made in pediatric or geriatric groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was in accordance with the previous studies by Patidar et al, 12 Murphy and Frigo, 14 and Lobo et al, 15 but differed from studies carried out by Lin and Lin. 16 The reason may be higher number of adults visiting the hospital outpatients department or being hospitalized and dose adjustments made in pediatric or geriatric groups.…”
Section: Discussionsupporting
confidence: 81%
“…In India also ADRs have emerged as leading killers. 12 The foremost objective of PvPI was to facilitate and improve the reporting of ADRs in India and to promote patients' safety. 13 Establishment of Pharmacovigilance units in the Medical College and hospitals has facilitated the spontaneous reporting of ADRs to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the high morbidity in adult population may be because of multi drug therapy or other disease like hypertension, diabetes, asthma or other chronic diseases. Our finding similar with the finding of Patidar et al, Murphy et al 6,8 The most common category associated with ADRs was skin (46.55%). This finding is consistent with the study by Coelho et al, Fredy et al, Rajesh et al, but it differs from reports of Suh et al where gastrointestinal manifestations had the highest rate, which was second highest in our study (30.45%).…”
Section: Discussionsupporting
confidence: 83%
“…5 Patidar et al observed that the occurrence of ADRs was (45.94%) in men and (54.05%) in women. 6 Other studies by Sriram et al, Richa, VR Tandon et al reported that males have greater risk of ADR than females. 12,15 There are various factors like age of patients, gender, number of drug taken, duration of hospital admission, genetic factors, ethnicity, dietary, and environmental factors affecting the ADR incidence.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend has been reported in other studies. 14,15 The common ADRs shown by patients were rashes, itching, respiratory distress, diarrhoea and fever. This pattern has been reported in other study also.…”
Section: Discussionmentioning
confidence: 99%